KONTRUKSI BERITA KEBUDAYAAN HUMAS KOTA PALEMBANG PADA WEBSTITE: bakohumas.palembang.go.id - eka yati, Sri; Budi Santoso; Arif Ardiansyah; Hamzah (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2023)
Local culture is an important element in a society. Local culture must be maintained and protected, just like the local culture in Palembang City. Songket weaving culture is one of the most valuable regional cultural assets in Palembang City. Songket weaving itself is a tradition carried out by the people of Palembang. One of the activities carried out by the Palembang City government through Palembang City Public Relations is to make news about the local culture of Palembang City (Songket Weaving). The news was published on online media or the Palembang City Public Relations website www.bakohumas.palembang.go.id. Based on the results of the study, it was found that the local culture of Palembang City, namely songket woven fabric, was published in online media or the Palembang City Public Relations website www.bakohumas.palembang.go.id. With the title